Utility of blue-on-yellow perimetry in the evaluation of patients with idiopathic optic neuropathy - Makino S (Dove Medical Press, 2013)
Shinji MakinoDepartment of Ophthalmology, Jichi Medical University, Shimotsuke, Tochigi, JapanAbstract: A 68-year-old woman with bilateral idiopathic optic neuropathy was examined using blue-on-yellow perimetry. Best-corrected visual acuity was 0.5 and 0.6 in her right and left eyes, respectively. Visual field testing with a Goldmann perimeter showed constriction of the I/2 e isopter in both eyes. With regard to mean deviation, the results (–13.18 dB right, –10.01 dB left) of blue-on-yellow perimetry were worse than those obtained using white-on-white perimetry (–1.26 dB right, –1.83 dB left). Optical coherence tomography revealed decreased retinal nerve fiber layer thickness in both eyes. Blue-on-yellow perimetry is useful for the detection of visual field disturbances in patients with optic neuropathy.Keywords: optic neuropathy, blue-on-yellow perimetry, white-on-white perimetry, optical coherence tomography, retinal thickness.